STRATEGI PENGALIHAN SUMBER ENERGI BERBASIS BBM MENJADI ENERGI TERBARUKAN Studi Kasus di PT PLN (Persero) - , Muhammad Ade Irfan; , Dr. Hargo Utomo, MBA., M.Com. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to find out the formulate strategies in responding to the transfer of fuel oil using renewable energy fuels are hydropower and geothermal power which to find source and obstacle renewable energy, find electricity ratio area, identification power plant on locations, and then the strategy. Indonesia have a problem on the blackout condition because of lack of fuel oil to generate power plant. The condition of rolling blackouts in some areas due to lack of availability fuel oil. Power Plant use fuel oil in Indonesia is very vulnerable to the tendency of scarcity. Other countries also require the availability and continuity with the trend of rising fuel energy economy. This causes a problem is encountered that is the availability of electrical energy is not sustainable. So that the necessary diversion strategy to ensure sustainability of the power plant remains in operation. Availability of electrical energy must be available at any time, place, and sufficient, barriers to access to electrical energy must be eliminated. Energy used and performed a backup to the availability and continued. Oil-based energy is very dependent on the security of supply, availability in the country - the oil producing countries, and up - down world market oil prices. Manufacture of electrical energy providers are still based on oil because the infrastructure in Indonesia and the world still use the fuel as energy, the conditions of supply - demand for fuel energy industry is still crippled cause - the industry is reluctant to move energy. So this study focused on the provision of case studies on energy generation system of PT. PLN (Persero). The data retrieved, sorted, and analyzed in accordance with the designation. The results that the transfer of renewable energy strategy done to the area in Eastern Indonesia (IBT), incentives to use renewable energy, and cooperation with local governments and related institutions will facilitate the transfer of fuel to renewable energy.